2020
DOI: 10.1088/1757-899x/890/1/012173
|View full text |Cite
|
Sign up to set email alerts
|

Engineering and computer graphics for effective training in a construction university

Abstract: One of the most important disciplines for the training of civil engineers is engineering and computer graphics. However, traditional training in engineering graphics does not bring tangible results, so there is a need for the introduction of modern innovative approaches and methods. It is proposed and justified the use of a combined approach to teaching engineering graphics, based on the combination of three-dimensional modeling in AutoCAD 2018 and traditional, on paper, manually. Studies conducted on the basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Our experiment [25] has shown that the most effective way is to draw the part in a computer programme and then, having an idea of it, to draw it on a sheet of paper. This way, the student can visualize the model of the part in advance and it will be easier for him to draw it on the sheet of paper.…”
Section: Resultsmentioning
confidence: 99%
“…Our experiment [25] has shown that the most effective way is to draw the part in a computer programme and then, having an idea of it, to draw it on a sheet of paper. This way, the student can visualize the model of the part in advance and it will be easier for him to draw it on the sheet of paper.…”
Section: Resultsmentioning
confidence: 99%
“…The development of spatial-design thinking through the study of geometry and graphics complements the methods of applying layout and graphic computer programs used in architectural schools in Europe and America. Modern methods of displaying space cannot be imagined without parametric modeling, but this aspect does not exclude the development of spatial-design thinking [3,[25][26][27]. Architectural innovation requires combining a simple understanding of space and evolutionary design actions, which would allow moving in a given.…”
Section: Resultsmentioning
confidence: 99%
“…Existing graphic disciplines are associated with the formation of students' skills to perform drawings and are considered as a prerequisite for further professional training, which is associated with graphic knowledge and skills. There is a contradiction between the increasing role of graphic information in the life of society and the insufficient use of the potential of graphic educational disciplines for the development of mental operations as elements of the graphic culture of students [4].…”
Section: Introductionmentioning
confidence: 99%